طرق تلقي الحديث عند الصحابة رضوان الله غليهم بعد مماته صلى الله عليه وسلم - Shumsudin Yabi; Norhasnira Ibrahim; Aminudin Basir@Ahmad; Fadlan bin Mohd Othman; Ali Samoh; Akila Mamat (Universiti Kebangsaan Malaysia (UKM), 2024)
Non-Indexed Publication